Consumer Buying Intention Towards Health Insurance Products:AQualitative Perspective (International Journal of Food and Nutritional Sciences, 2022)
Good health is the most important and valuable asset for humans, and health insuranceisanessential type of insurance that provides financial protection to an individual and their familyatthe time of some uncertain risks or damages caused to health. Health insurance provides safetyand protection to a person and encourages them to save money to treat health issues.